The role of prosodic skills in developmental language disorder. A case study - González-Alba, Beatriz; Calet, Nuria (Revista de Investigación en Logopedia, 2021)
Several studies point out that prosody, or the phonology subsystem that encompasses the rhythmic and melodic characteristics of language, is a key aspect of language processing. Hence, recent studies show deficits in this area in children with developmental language disorder (DLD). However, the research findings that have been reported are contradictory, and in the case of Spanish the studies are very scarce. The aim of this case study is to analyze the profile of prosodic skills, receptive and expressive, through a full prosodic battery and a lexical stress sensitivity task of a child with a DLD. This participant is 8 years old and belongs to a medium socio-economic level. His performance was compared with that of a control participant of the same chronological age, socio-economic level and without difficulties. In addition, verbal and non-verbal intelligence skills, various language skills, as well as reading skills were assessed. The results show that the participant with TDL presents difficulties in some prosodic skills (Turn-End input, Focus Output, Short-item Discrimination and Expressive Long Item Imitation). The implications of the results obtained from this qualitative research on the importance of considering prosodic skills in the assessment of TDL are discussed. Future studies with a larger sample are needed to corroborate these findings and further analyze the role of prosody in TDL in Spanish.